VD_FINDINFO Jug / 2021 / 465 vom 2. August 2021 - VD Tribunal cantonal (2021)
PRÉSOMPTION D'INNOCENCE, APPRÉCIATION DES PREUVES, COAUTEURDROIT PÉNAL, COMMERCE DE STUPÉFIANTS, REJET DE LA DEMANDE | 10 CPP (CH)